2009
DOI: 10.2165/0148581-200911010-00012
|View full text |Cite
|
Sign up to set email alerts
|

Pediatric Clinical Pharmacology Studies in Chagas Disease

Abstract: Chagas disease is a neglected parasitic disease endemic in the Americas. It mainly affects impoverished populations and the acute phase of the infection mostly affects children. Many cases have also been detected in nonendemic countries as a result of recent migratory trends. The chronic phase is relatively asymptomatic, but 30% of patients with chronic infection eventually develop cardiac and digestive complications that commonly lead to death or disability. Only two drugs are available for the treatment of C… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

0
26
0

Year Published

2009
2009
2024
2024

Publication Types

Select...
7
2

Relationship

5
4

Authors

Journals

citations
Cited by 23 publications
(26 citation statements)
references
References 41 publications
0
26
0
Order By: Relevance
“…During the past decade, numerous pharmacological studies have demonstrated the existence of significant pharmacokinetic and pharmacodynamic differences between adults and children (Reed 1999, Standing & Tuleu 2005 and studies describing the kinetics of benznidazole are being carrying out (Garcia-Bournissen et al 2009). Every year, the National Chagas Programs detect thousands of children infected in the chronic or earlier stages who require treatment.…”
Section: New Ways To Address Old Needsmentioning
confidence: 99%
“…During the past decade, numerous pharmacological studies have demonstrated the existence of significant pharmacokinetic and pharmacodynamic differences between adults and children (Reed 1999, Standing & Tuleu 2005 and studies describing the kinetics of benznidazole are being carrying out (Garcia-Bournissen et al 2009). Every year, the National Chagas Programs detect thousands of children infected in the chronic or earlier stages who require treatment.…”
Section: New Ways To Address Old Needsmentioning
confidence: 99%
“…Even though both drugs were developed over 4 decades ago, there is little information available on their clinical pharmacology, particularly for special populations such as children [8], [9]…”
Section: Introductionmentioning
confidence: 99%
“…2 Initial infections with T. cruzi take place mostly in children, by vector or congenital transmission. 3 As vector control improves, congenital transmission is rapidly becoming the main route of infection, highlighting the importance of the diagnosis of maternal infection. However, in view of the particular cultural and social context of endemic Chagas disease regions, this diagnosis is frequently associated with pregnancy screening or birth attendance.…”
Section: Introductionmentioning
confidence: 99%